Histological type of focal cortical dysplasia is associated with the risk of postsurgical seizure in children and adolescents - Chen J; Huang Z; Li L; Ren L; Wang Y (Dove Medical Press, 2019)
Jia Chen,1,2 Zhaoyang Huang,1,2 Liping Li,1,2 Liankun Ren,1,2 Yuping Wang1,21Department of Neurology, Xuanwu Hospital, Capital Medical University, Beijing 100053, People’s Republic of China; 2Beijing Key Laboratory of Neuromodulation, Beijing 100053, People’s Republic of ChinaAim: Focal cortical dysplasia (FCD) is a common cause of refractory epilepsy in children and adolescents. Epilepsy surgery is a treatment option for FCD. This study aimed to investigate the relationship between postsurgical outcomes and FCD types according to the International League Against Epilepsy (ILAE) classification and assess prognostic factors in pediatric and adolescent epilepsy surgery.Methods: We retrospectively analyzed 92 children and adolescents with a proven pathological diagnosis of FCD who underwent resective surgery at our epilepsy center between August 2012 and September 2015. The patients were followed up for at least 1 year to evaluate the surgical outcomes, and a multivariable regression analysis was performed to identify risk factors of seizure relapse.Results: After surgery, 53.3% of the patients were completely seizure-free during the entire follow-up period. The FCD types, incomplete resection of the epileptic cortex, and use of intracranial electrode were independent risk factors of seizure recurrence. The patients with FCD type II had relatively favorable surgical outcomes compared to the patients with FCD type I. The difference in the postoperative outcome between patients with FCD types III and I was not significant.Conclusion: There is a significant association between FCD types and surgical outcomes in children and adolescents with epilepsy. These findings provide guidance for the optimization of surgical strategies.Keywords: epilepsy, focal cortical dysplasia, surgery, outcome, children, adolescent